2022
DOI: 10.1186/s12889-022-12696-x
|View full text |Cite
|
Sign up to set email alerts
|

Determining intention, fast food consumption and their related factors among university students by using a behavior change theory

Abstract: Background Today, with the advancement of science, technology and industry, people’s lifestyles such as the pattern of people’s food, have changed from traditional foods to fast foods. The aim of this survey was to examine and identify factors influencing intent to use fast foods and behavior of fast food intake among students based on the theory of planned behavior (TPB). Methods A cross-sectional study was conducted among 229 university students.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 33 publications
6
15
1
Order By: Relevance
“…According to Seo et al (2011), behavioural intention and perceived behavioural control were significantly associated to fast-food consumption behaviour. This was currently supported by a study done among Medical Sciences students whereby behavioural intention was found to be highly correlated to fast food consumption with behavioural intention variable demonstrated greater significance in the association (Didarloo et al, 2022). Therefore, it can be concluded that based on this analysis, it was found that students from each faculty either FKP or FHPK, have contradicting determinants of their fast-food consumption behaviour, marking the achievement of research objective two.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…According to Seo et al (2011), behavioural intention and perceived behavioural control were significantly associated to fast-food consumption behaviour. This was currently supported by a study done among Medical Sciences students whereby behavioural intention was found to be highly correlated to fast food consumption with behavioural intention variable demonstrated greater significance in the association (Didarloo et al, 2022). Therefore, it can be concluded that based on this analysis, it was found that students from each faculty either FKP or FHPK, have contradicting determinants of their fast-food consumption behaviour, marking the achievement of research objective two.…”
Section: Resultssupporting
confidence: 53%
“…These outputs also confirmed that the dimensions of TPB were strongly related to fastfood consumption behaviour; reflecting how individuals' attitude, behavioural subjective norms and perceived behavioural control can influence their fast-food consumption behaviour. Cited by Didarloo et al (2022), eating habits and behaviours can be predicted by TPB, which has also garnered the researchers' attention in recognizing beliefs and norms that are related to the fast-food consumption. Nevertheless, correlational analysis results involved FHPK showed that it has higher coefficient values as compared to FKP, which may be due to having a wellness program in the faculty, reflecting they are more health conscious and have better health awareness.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that women with lower income had a higher mean BMI. 11 Around 48% of responders ingest fast food during lunchtime, 37.0% during the evening, and 9.8% during dinner with a frequency of twice a week for more than 90% of the responders. Similar results were reported for college students at the Midwestern land-grant university, where most students eat fast food during lunchtime at least once per week.…”
Section: Discussionmentioning
confidence: 98%
“…Foods made with lower nutritional value are classi ed as such by Seo, Lee, and Nam (2011). Fast-Food Consumption is linked to unsatisfactory nutrients intake and unhealthy dietary behaviors that increased the incidence of non-communicable diseases in the worldwide (Didarloo, Khalili, Aghapour, Moghaddam, & Mousavi, 2022). Globally, the consumption of fast food has signi cantly increased among people of different ages (AlTamimi et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, over 124 million children and adolescents, of whom 14% were obese (World Health Organization: WHO, 2021), and the gure is predicted to reach 2.7 billion by 2025 according to the WHO (Shori, Albaik, & Bokhari, 2017). In a study conducted in the United States on adolescents between the ages of 13 and 17, a signi cant relationship was found between overweight and processed foods (Didarloo et al, 2022).…”
Section: Introductionmentioning
confidence: 99%